Tradisi Longkangan Sebagai Konvensi Budaya Lokal dan Agama Islam di Desa Binade Kecamatan Ngrayun Kabupaten Ponorogo - Erwin Yudi Prahara; Waris Waris; Eko Saputro (MA'ALIM: Jurnal Pendidikan Islam, 2022)
One of the traditions that includes local culture in Ponorogo is the Longkangan Tradition. The existence of the longkangan tradition has had various impacts on the lives of the people of Binade village, Ngrayun Ponorogo sub-district, mainly in the relationship between Islam and Javanese tradition which eventually formed a convention. This research uses a qualitative descriptive approach that explains the community's perceptions and the existence of local cultural and Islamic religious conventions in the Longkangan tradition. In this study, it was found that the people of Binade village as a whole are Muslim and come from Javanese tribes. Nearly all Binade villagers take water from the river or Belik. Therefore, the Longkangan tradition emerged, which aims to bring gratitude to God for the abundance of water sources for the community. In addition, the longkangan tradition also aims to commemorate services and pray for the spirits of the ancestors who have opened villages and water sources in Binade village. The conclusion of this research is that the conventions or agreements that exist in the longkangan tradition are still being obeyed by the Binade village community. In this case there is no written law regulating the longkangan tradition, but the existence of this convention has made the longkangan tradition still preserved until now. Until now the Longkangan tradition is still preserved as a convention of local culture and Islam.